2001
DOI: 10.1542/peds.108.5.1175
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Lispro Lowers Postprandial Glucose in Prepubertal Children With Diabetes

Abstract: In prepubertal children, insulin lispro given before meals is safe and significantly lowers postprandial glucose levels after breakfast and dinner compared with regular human insulin, and insulin lispro given after the meal provides similar benefits as regular human insulin before the meal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0
4

Year Published

2003
2003
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 13 publications
5
77
0
4
Order By: Relevance
“…A further 15 studies were excluded from this analysis. Of these, five were performed with patients with type 2 diabetes [23,24,25,26,27], three were performed with children [28,29,30], one with adolescents [31], one with children and adults [32], one with pregnant type 1 diabetic patients [33], two with patients with gestational diabetes [34,35] and two duplicate publications did not provide further information on prespecified outcome measures [36,37]. We ultimately identified 27 randomised controlled trials that compared SAI analogues with regular insulin using either CSII or IIT as injection regimens.…”
Section: Resultsmentioning
confidence: 99%
“…A further 15 studies were excluded from this analysis. Of these, five were performed with patients with type 2 diabetes [23,24,25,26,27], three were performed with children [28,29,30], one with adolescents [31], one with children and adults [32], one with pregnant type 1 diabetic patients [33], two with patients with gestational diabetes [34,35] and two duplicate publications did not provide further information on prespecified outcome measures [36,37]. We ultimately identified 27 randomised controlled trials that compared SAI analogues with regular insulin using either CSII or IIT as injection regimens.…”
Section: Resultsmentioning
confidence: 99%
“…The number of patients in each study ranged from 7 to 1008. Of the 48 crossover studies, 19,20,24,25,30,32,33,35,[37][38][39][42][43][44][45]47,48,51,55,56,58,[62][63][64][65][66][67][69][70][71][72][73][74]78,79,[81][82][83]85,87,89,93,96,[100][101][102]121 most lacked or did not mention a washout period. All studies were of open-label design.…”
Section: Study Characteristics and Methodologic Qualitymentioning
confidence: 99%
“…Dosing with lispro after meals allows a care provider to more accurately titrate the insulin doses for an erratic eater, with the goal of matching actual food intake and insulin more closely and minimizing the potential for hypoglycemia. Other studies have shown that in the child with more predictable eating habits, premeal insulin dosing results in lower postprandial blood glucose values (65).…”
Section: Basal Bolus Insulin Regimensmentioning
confidence: 97%